Intrinsic Characteristics of Neighboring DNA Modulate Transposable Element Activity in Drosophila melanogaster. - Esnault, C.; Palavesam, A.; Pilitt, K.; O'Brochta, D.A. (Genetics, 2011)
Identifying factors influencing transposable element activity is essential for understanding how these elements impact genomes and their evolution as well as for fully exploiting them as functional genomics tools and gene-therapy vectors. Using a genetics-based approach, the influence of genomic position on piggyBac mobility in Drosophila melanogaster was assessed while controlling for element structure, genetic background, and transposase concentration. The mobility of piggyBac elements varied over more than two orders of magnitude solely as a result of their locations within the genome. The influence of genomic position on element activities was independent of factors resulting in position-dependent transgene expression ("position effects"). Elements could be relocated to new genomic locations without altering their activity if ? 500 bp of genomic DNA originally flanking the element was also relocated. Local intrinsic factors within the neighboring DNA that determined the activity of piggyBac elements were portable not only within the genome but also when elements were moved to plasmids. The predicted bendability of the first 50 bp flanking the 5' and 3' termini of piggyBac elements could account for 60% of the variance in position-dependent activity observed among elements. These results are significant because positional influences on transposable element activities will impact patterns of accumulation of elements within genomes. Manipulating and controlling the local sequence context of piggyBac elements could be a powerful, novel way of optimizing gene vector activity.